Molecular prevalence of extended spectrum beta lactamase producing Escherichia coli in dressed broiler chickens in Sokoto metropolis - Mukhtar Kabir; Muhammad Sanusi Yahaya; Abdulbariu Ogirima Uhuami; Yusuf Yakubu; Abdurrahman Hassan Jibril (The Microbe, 2025)
Chickens are a key source of meat in Sokoto, Nigeria. However, excessive antibiotic use in poultry farming has led to antimicrobial resistance (AMR), particularly in Escherichia coli, which can acquire Extended Spectrum Beta-Lactamase (ESBL) resistance genes. This study investigates the molecular prevalence of ESBL-producing E. coli in dressed broiler chickens sold in Sokoto metropolis, Nigeria. A cross-sectional study design was used to collect 165 carcass rinsate samples from broiler chickens using systematic random sampling. E. coli was isolated through culture on MacConkey and Eosin Methylene Blue agar, followed by biochemical characterization using IMViC tests. Molecular confirmation of E. coli was performed by PCR targeting the uidA gene. Confirmed E.coli were subjected phenotypic screening for the production of ESBL using the Double Disk Synergy Test (DDST). Isolates that were phenotypically ESBL producers were subjected to PCR detection of blaTEM, blaSHV, and blaCTX-M resistance genes. Phenotypic screening for ESBL production found 10 cephalosporin-resistant isolates, all of which tested positive using the DDST. Molecular analysis revealed ESBL genes in 33.3 % (9/27) of isolates, with blaTEM detected in 8 (29.6 %), and blaSHV and blaCTX-M in 3 (11.1 %) respectively. One isolate harbored all three genes, three harbored two, and five contained only one type of ESBL gene. The identification of ESBL producing E. coli in poultry that is ready for the market emphasizes the urgent need for molecular surveillance, more stringent laws governing the use of antibiotics in animal husbandry, and greater public education in order to reduce the risks of AMR in food systems.